ANALISIS KEMAMPUAN TEKNIK DASAR PASSING BAWAH SISWA PESERTA EKSTRAKURIKULER BOLA VOLI DI SDN KARANGHARJA II KABUPATEN TANGERANG - Dwi Nokhriyana, Aditya; Zuliani, Rizki; Puspita Rini, Candra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the basic passing technique abilities of students participating in extracurricular volleyball. This research uses qualitative descriptive. The subjects in this research were all students participating in extracurricular volleyball at SDN Karangharja II, totaling 16 students. Data collection techniques use observation, interviews and documentation to determine the basic passing technique abilities of each individual. The results of this study showed that of the 8 male students participating in extracurricular volleyball, 6 of the participating students were able to position their fingers and arms correctly, body position well and correctly, hit the ball correctly and have a good final stance so that the passing ability of the 6 participating students the quality is very good. However, the 2 student participants were not able to perform finger and arm positions, body positions, contact with the ball, and the final stance was not correct so that their lower passing ability was of poor quality. Meanwhile, 1 female student participant was able to position her fingers and arms correctly, body position well and correctly, hit the ball correctly and have a good final stance so that the down passing ability of 1 student participant was of very good quality. However, the 7 female student participants were not able to perform finger and arm positions, body positions, contact with the ball, and the final stance was not correct so that their lower passing ability was not of good quality. Keywords: Basic technical abilities, under passing, volleyball, extracurrculars, Elementary school students